Corruption as an Empty Signifier Politics and Political Order in Africa - Koechlin, Lucy (Brill, 2013)
Corruption as an Empty Signifier critically explores the ways in which corruption in Africa has been equated with African politics and political order, and offers a novel approach to understanding corruption as a potentially emancipatory discourse of political transformation. Conventionally, both academic literature as well as development policies depict corruption as the lynchpin of politics in Africa, locking African societies into political orders which subvert democratic change.